2014
DOI: 10.3109/10837450.2014.910810
|View full text |Cite
|
Sign up to set email alerts
|

Matrix tablets based on a carrageenan with the modified-release of sodium riboflavin 5′-phosphate

Abstract: The focus of this work was to produce modified-release monolithic matrix tablets containing sodium riboflavin 5'-phosphate (vitamin B2) as active pharmaceutical ingredient (API). Riboflavin 5'-phosphate is absorbed from the upper gastrointestinal tract by a specific transport mechanism. The aim of this work was the development of modified-release tablets from which most or the entire API can dissolve within 5 h. The dissolution was started in medium pH 1.2 (gastric juice) and finished in medium pH 4.5. The mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In another approach, carrageenan was associated with two drug models, diltiazem HCl and metoprolol tartrate, and the two studied complexes released the drug with different mechanism indicating two different drug/polymer interaction strengths (stronger interaction with diltiazem) [ 259 ]. Other recent developments included the use of carrageenan, combined with other matrix materials, to associate and release vitamin B2 [ 260 ] and lisinopril [ 261 ].…”
Section: Drug Delivery Systems Based On Seaweed Sulfated Polysacchmentioning
confidence: 99%
“…In another approach, carrageenan was associated with two drug models, diltiazem HCl and metoprolol tartrate, and the two studied complexes released the drug with different mechanism indicating two different drug/polymer interaction strengths (stronger interaction with diltiazem) [ 259 ]. Other recent developments included the use of carrageenan, combined with other matrix materials, to associate and release vitamin B2 [ 260 ] and lisinopril [ 261 ].…”
Section: Drug Delivery Systems Based On Seaweed Sulfated Polysacchmentioning
confidence: 99%
“…The release profile showed a uniform increase of up to 80%. Lactose influenced the behavior of the matrix; when there is less lactose, the elasticity of the matrix is greater, resulting in tablets with weak mechanical properties [ 134 ].…”
Section: Carrageenan In Biomedical Applicationsmentioning
confidence: 99%
“…Kasapis et al (2015) developed a carrier of ĸ-carrageenan/glucose syrup to control the release of thiamin (Vitamin B1) [30]. Buchholz et al (2015) reported modified-release matrix tablets based on carrageenan combined with microcrystalline cellulose and lactose, containing vitamin B2 [31]. Human skin is exposed to oxidative damage caused by free radicals, which is one of the main causes of skin aging.…”
Section: Introductionmentioning
confidence: 99%